Melanoma-associated mutations in protein phosphatase 6 cause chromosome instability and DNA damage owing to dysregulated Aurora-A. - Hammond, D; Zeng, K; Espert, A; Bastos, R; Baron, R; Gruneberg, U; Barr, F (2013)
Mutations in the PPP6C catalytic subunit of protein phosphatase 6 (PP6) are drivers for the development of melanoma. Here, we analyse a panel of melanoma-associated mutations in PPP6C and find that these generally compromise assembly of the PP6 holoenzyme and catalytic activity towards a model substrate. Detailed analysis of one mutant, PPP6C-H114Y, in both primary melanoma and engineered cell lines reveals it is destabilized and undergoes increased proteasome-mediated turnover. Global analysis of phosphatase substrates by mass spectrometry identifies the oncogenic kinase Aurora-A as the major PP6 substrate that is dysregulated under these conditions. Accordingly, cells lacking PPP6C or carrying the PPP6C-H114Y allele have elevated Aurora-A kinase activity and display chromosome instability with associated Aurora-A-dependent micronucleation. Chromosomes mis-segregated to these micronuclei are preferentially stained by the DNA damage marker γ-H2AX, suggesting that loss of PPP6C promotes both chromosome instability and DNA damage. These findings support the view that formation of micronuclei rather than chromosome instability alone explains how loss of PPP6C, and more generally mitotic spindle and centrosome defects, can act as drivers for genome instability in melanoma and other cancers.